Good Guys - Smith, David; Johnson, W. (Ascent Audio, 2020)
Women are at a disadvantage in the workplace, where they deal with unequal pay, sexual harassment, lack of credit for their contributions, and more. And while organizations are looking to address these issues, too many gender-inclusion initiatives focus exclusively on how women should respond, leaving men out of the equation. Such efforts reinforce the perception that these are "women's issues" and that men-often the most powerful stakeholders in an organization-don't need to be involved. As gender-in-the-workplace experts David G. Smith and W. Brad Johnson show in this important book, men have a crucial opportunity to promote gender equality at work. Research shows that when men are deliberately engaged in gender-inclusion programs, ninety-six percent of women in those organizations perceive real progress in gender equality, compared with only thirty percent of women in organizations without strong male engagement. Good Guys is the first book to provide a practical, research-based guide for how to be a male ally to women in the workplace. Filled with firsthand accounts from both men and women, as well as tips for getting started, the book shows how men can partner with their female colleagues to advance women's leadership and equality.